Continuity and change in the generalist cadre in Bangladesh: an analysis of recruitment and post-entry training in BCS ( Admin) - Momtaz, Salma (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Governance and Development, 2006.